A novel co-prime MIMO radar model for DOA estimation - Liu, Donghe; Zhao, Yongbo; Dong, Shuxian (Signal processing, 2022)
•The proposed co-prime MIMO radar model is based on the transmit energy focusing technique, which improves the signal-to-noise ratio (SNR) gain in the desired sector.•The transmit beamspace matrix with a specific structure is designed to ensure the number of DOFs is not sacrificed.•The CRB of the DOA estimation for the TEF-based co-prime MIMO radar has a lower bound than the traditional co-prime MIMO radar. In this paper, we propose a novel co-prime multiple-input multiple-output (MIMO) radar model based on the transmit energy focusing (TEF) technique for direction of arrival (DOA) estimation. Compared with omnidirectional radiation of the transmit energy of the traditional co-prime MIMO radar, the proposed model can focus the transmit energy in the desired spatial sector. To obtain more degrees of freedom (DOFs), we design the transmit beamspace matrix with a specific structure. Then, the sum and difference co-array (SDC) is given by vectorizing the sampling covariance matrix of the received data. Subsequently, the maximum number of consecutive lags and unique lags for SDC is derived. Besides, we also derive the Cramer–Rao bound (CRB) of our model. Moreover, the DOA estimation performance of the TEF-based co-prime MIMO radar and traditional co-prime MIMO radar is compared by using forward-backward spatial smoothing (FBSS), sparse recovery (SR), and fast iterative interpolated beamformer (FIIB) algorithms. Simulation results show the superiority of the proposed model.